2016 IEEE Power and Energy Conference at Illinois (PECI) 2016
DOI: 10.1109/peci.2016.7459256
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for the creation of geographically realistic synthetic power flow models

Abstract: To enable greater innovation in power systems, our research seeks to create entirely fictitious synthetic power system networks that capture the functionality, topology, and defining characteristics of the actual U.S. transmission system, and thus provide realistic test cases for research, without revealing any sensitive information. Creation of these models relies only on publicly available data and statistics derived from the actual grid. This paper outlines two fundamental steps for the creation of syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 5 publications
(6 reference statements)
0
37
0
Order By: Relevance
“…For example, in 2005 Xia et al [21] developed 9-bus and 179-bus transmission test systems that were then used by Chatterjee and Ghosh [22] (among others) to conduct transient stability studies. Gegner et al [23] propose a new method for the construction of transmission test systems.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…For example, in 2005 Xia et al [21] developed 9-bus and 179-bus transmission test systems that were then used by Chatterjee and Ghosh [22] (among others) to conduct transient stability studies. Gegner et al [23] propose a new method for the construction of transmission test systems.…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Works [7], [8], [9] provide readers more details on geographic substation placement, synthetic transmission line topology design and line parameter determination. As summarized in Fig.1, the network construction process is based on the statistics summarized from EI case, geographic relations, location-dependent load levels and generation capacities.…”
Section: Reviews Of the Creation Of Synthetic Transmission Networkmentioning
confidence: 99%
“…Until recently, there was limited work focusing on the creation of synthetic large-scale power system models using publicly available data to mimic the full complexity of today's electricity grids for energy economic studies. Our previous works [7], [8], [9] presented a methodology to create entirely fictitious synthetic power system networks that capture structural and functional characteristics of actual power grids 1 . To enable greater innovation on electricity markets, this paper aims to augment the synthetic power system networks with generator cost data, and thus provides realistic test cases for energy economic studies without revealing any sensitive information.…”
Section: Introductionmentioning
confidence: 99%
“…Authors in [20] reported some initial study results on the statistics of transmission line parameters. The substation placement method and transmission lines assignment based on population and energy data in [21] uses the methodology introduced in [22], [23], where they employ a clustering technique to ensure that synthetic substations meet realistic proportions of load and generation. [24] addressed the need for synthetic large-scale system dynamic models for transient stability studies such as wide-area damping control in [25], [26] and dynamic control allocation for damping of inter-area oscillations in [27].…”
Section: Introductionmentioning
confidence: 99%